The United Kingdom - Szczudlik, Justyna (The Role of Regions in EU-China Relations, 2021)
The aim of this chapter is to analyse how the UK actors cooperate with their Chinese counterparts at the regional and local level. Due to the United Kingdom’s constitutional and administrative structure, consisting of the four nations (countries), i.e. England, Wales, Scotland (collectively known as the Great Britain) and Northern Ireland, and a highly developed (yet asymmetrical) model of decentralisation of executive and legislative powers (known as devolution) within those four nations, in the UK’s case Sino-British local cooperation refers either to the nations themselves (e.g. Scotland), to various metropolitan projects in England (e.g. the Northern Powerhouse) or to individual cities. This chapter undertakes to answer the following questions: Do local authorities in the UK follow the central government’s policy on China? What are the British local governments’ main goals and areas of cooperation with their Chinese partners? What is the model of the UK’s paradiplomacy? The chapter consists of two main parts. The first one is devoted to the central level: the description of the UK government’s policy towards China, the state of play of UK-China relations, and the UK’s perception of China, including China’s “soft” presence in Britain (tourists, students, Confucius Institutes, etc.). The second part is focused on the local and regional level. It starts with an explanation of the legal framework of British local and regional level cooperation, then it sets forth the survey results, concluding with the presentation of two case studies: Liverpool – a city in England; and Scotland – one of the UK’s nations and EU regions.